Global survey of alternative splicing and gene modules associated with fertility regulation in a thermosensitive genic male sterile wheat - Bai, Jianfang (Journal of experimental botany, 2022)
© The Author(s) 2021. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.